HOLISTIC MANAGEMENT OF 63 YEARS OLD GERIATRIC MAN WITH AXIAL NECK PAIN THROUGH THE FAMILY MEDICINE APPROACH - Hana Nafisah; Clara FIrhan Asifa; Dian Isti Angraini (CV. Jasa Sukses Abadi, 2023)
The most common health problem at work is musculoskeletal disorders (MSDs). One of the most common complaints of MSDs is pain in the neck muscles or axial neck pain. Axial neck pain is often exacerbated and has many risk factors, especially related to workplace ergonomics. Comprehensive management is needed so that risk factors can be identified, and holistic management can be given. Application of evidence-based medicine-based family doctor services by identifying risk factors, clinical problems, and patient management based on a patient problem-solving framework using a patient-centered and family approach. Primary data were obtained through anamnesis, physical examination, supporting examinations and home visits to assess the physical environment. The patient complains of pain in the back of the neck accompanied by a feeling of stiffness in the neck. Complaints felt since 1 week ago. The pain is felt like squeezing, comes and goes, decreases slightly when you apply warm oil and rest, but a few moments later the pain will recur, the pain gets worse after working lifting heavy weights on your shoulders or turning your neck to the right and left and lowering your head. Pain also radiates from the back of the neck to the shoulders, shoulder blades and upper back. Pain does not radiate down the arm. According to the patient's statement, the pain scale felt by the patient between 1-10 is 7. Diagnosis and management of this patient is carried out holistically and comprehensively, patient center, family appropriate, community oriented with drug administration, carrying out ergonomic guidelines at work and doing cervical exercises regularly according to the EBM so that it can prevent recurrence of axial neck pain.